Secondary battery, preparation method of secondary battery and electronic device
By setting a double-layer material layer on the single-side outer electrode sheet of the electrode assembly of the lithium-ion battery, the types and content of materials and adhesives are regulated, the problems of black spots and lithium extraction during the circulation are solved, and the circulation performance and safety of the battery are improved sex.
Patent Information
- Application Number
- CN202411215660.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-31
AI Technical Summary
The manufacturing process and structure of single-sided coated electrode sheets in lithium-ion batteries lead to prone to black spots or lithium extraction during the cycle, which reduces the performance of the battery.
A double-layer material layer is provided on the single-side outer electrode sheet of the electrode assembly so that its conductivity is less than or equal to the conductivity of the inner electrode sheet, and the types and content of active materials and adhesives are regulated, so as to increase the impedance of the outer electrode sheet to slow down the Electrolyte consumption rate.
It effectively reduces the risk of black spots and lithium excretion on the outer electrode plate of the electrode assembly, and improves the circulation and safety performance of the secondary battery.
Smart Images

Figure CN119170853A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery, a method for preparing a secondary battery, and an electronic device. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, have the characteristics of large specific energy, high operating voltage, low self-discharge rate, small size and light weight, and are widely used in the field of consumer electronics.
[0003] At present, the electrode assembly in lithium-ion batteries often adopts a multi-electrode and laminated structure to reduce the battery impedance. Among them, in order to ensure the ultra-thinness and high energy density of lithium-ion batteries, the outermost electrode of the electrode assembly usually adopts a single-sided coated electrode. However, due to the manufacturing process and structural particularity of the single-sided coated electrode, black spots or lithium precipitation are prone to occur during the cycle, resulting in reduced performance of lithium-ion batteries. Summary of the invention
[0004] The purpose of the present application is to provide a secondary battery, a method for preparing a secondary battery and an electronic device, so as to reduce the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly and improve the cycle performance of the secondary battery.
[0005] It should be noted that in the invention content of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0006] At present, in order to reduce process costs and increase the energy density of secondary batteries, the outermost pole piece of the electrode assembly of the multi-pole stacking structure in lithium-ion batteries is usually a single-sided coated pole piece, that is, a material layer is set only on one side of the current collector of the pole piece, and the inner pole piece is usually a double-sided coated pole piece, and the material layer of the inner and outer pole pieces is the same, which will make the outer current density of the electrode assembly significantly higher than the inner current density. During the cycle of the secondary battery, the electrolyte consumption rate in the outer side of the electrode assembly is faster, and black spots or lithium deposition are prone to occur on the outer single-sided coated pole piece, resulting in a decrease in the cycle performance of the secondary battery and a decrease in safety performance. Based on this, the present application provides a secondary battery that can reduce the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly and improve the cycle performance of the secondary battery. The specific technical solution is as follows:
[0007] The first aspect of the present application provides a secondary battery, including an electrolyte, a shell and an electrode assembly of a laminate structure, along the thickness direction of the electrode assembly, the electrode assembly includes a first pole sheet, a second pole sheet and a diaphragm arranged between the first pole sheet and the second pole sheet; the electrode assembly also includes a first pole tab assembly and a second pole tab assembly, the first pole tab assembly includes a plurality of first pole tabs, the second pole tab assembly includes a plurality of second pole tabs, the plurality of first pole tabs correspond one-to-one to the first pole sheet, and the plurality of second pole tabs correspond one-to-one to the second pole sheet. The first pole piece includes two outer first pole pieces and at least one inner first pole piece. Along the thickness direction of the electrode assembly, the two outer first pole pieces are respectively located at the outermost two sides of the electrode assembly, and the inner first pole piece is located between the two outer first pole pieces; the first pole piece includes a first current collector and a first active material layer. The first current collector includes a first surface and a second surface arranged opposite to each other along the thickness direction of the electrode assembly. The first surface is closer to the shell than the second surface. The first surface and the second surface of the inner first pole piece are both provided with a first active material layer; at least one outer first pole piece is a single-sided first pole piece. The first surface of the single-sided first pole piece is not provided with a first active material layer, and the second surface of the single-sided first pole piece is provided with a first active material layer. The first active material layer arranged on the second surface of the single-sided first pole piece is composed of a first material layer and a second material layer arranged in a stacked manner, and the first material layer is located between the first current collector and the second material layer. The conductivity of the single-sided first pole piece is AS / cm, and the conductivity of the inner first pole piece is BS / cm, and A≤B. By setting a double-layer material layer on the single-sided outer electrode sheet of the electrode assembly and making the electrical conductivity of the single-sided outer electrode sheet less than or equal to the electrical conductivity of the inner first electrode sheet, the current density of the outer electrode sheet of the electrode assembly is reduced, thereby reducing the consumption rate of the electrolyte during the cycle, reducing the risk of black spots and lithium deposition on the outer electrode sheet of the electrode assembly during the cycle, and improving the cycle performance of the secondary battery.
[0008] In one embodiment of the present application, 0.3≤A / B≤1. In one embodiment of the present application, 0.65≤A / B≤1. By adjusting the value of A / B within the above range, it is helpful to reduce the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0009] In one embodiment of the present application, the first pole piece is a positive pole piece, which has a more obvious effect of reducing the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle, thereby further improving the cycle performance of the secondary battery.
[0010] In one embodiment of the present application, the first material layer includes a first active material, the first active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate or lithium manganate, and the second material layer includes a second active material, the second active material includes at least one of lithium cobaltate, lithium nickelate, lithium manganate, nickel cobalt manganese ternary material or lithium-rich manganese-based material. Compared with the outer pole piece of a conventional electrode assembly, the impedance of the outer pole piece of the electrode assembly is increased, thereby slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is conducive to reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0011] In one embodiment of the present application, the Dv50 of the first active material is 3μm to 25μm, and the Dv99 of the first active material is 10μm to 65μm; the Dv50 of the second active material is 4.5μm to 24.5μm, and the Dv99 of the second active material is 45μm to 65μm. By regulating the Dv50 and Dv99 of the first active material, the Dv50 and Dv99 of the second active material are within the above range, which is conducive to reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0012] In one embodiment of the present application, the first material layer includes a first binder, and the second material layer includes a second binder, and the first binder and the second binder are independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid; based on the mass of the first material layer, the mass percentage of the first binder is 0.5% to 5%, and based on the mass of the second material layer, the mass percentage of the second binder is 0.4% to 5%. By selecting the first binder and the second binder within the above-mentioned range, and regulating the mass percentage of the first binder and the mass percentage of the second binder within the above-mentioned range, it is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0013] In one embodiment of the present application, the first material layer includes a first conductive agent, the second material layer includes a second conductive agent, the first conductive agent and the second conductive agent are independently selected from at least one of conductive carbon black, carbon nanotubes, graphene or conductive graphite; based on the mass of the first material layer, the mass percentage of the first conductive agent is 1% to 10%, based on the mass of the second material layer, the mass percentage of the second conductive agent is 1% to 10%. By selecting the first conductive agent and the second conductive agent within the above-mentioned range, and regulating the mass percentage of the first conductive agent and the mass percentage of the second conductive agent within the above-mentioned range, it is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0014] In one embodiment of the present application, the first active material layer disposed on the first surface and the second surface of the inner first pole piece is a third material layer, the third material layer includes a third active material, the third active material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel cobalt manganese ternary material or lithium-rich manganese-based material, and the mass percentage of the third active material is 85% to 98.6% based on the mass of the third material layer. By selecting the third active material of the above type and regulating the mass percentage of the third active material within the above range, it is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, and the secondary battery has good cycle performance.
[0015] In one embodiment of the present application, the thickness of the first material layer is 20 μm to 60 μm, and the thickness of the second material layer is 20 μm to 150 μm. By regulating the thickness of the first material layer and the thickness of the second material layer within the above range, it is helpful to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, while taking into account the high energy density of the secondary battery, the cycle performance of the secondary battery is improved.
[0016] In one embodiment of the present application, the thickness of the third material layer is 80 μm to 250 μm. By adjusting the thickness of the third material layer within the above range, the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is reduced, and the secondary battery has a high energy density and good cycle performance.
[0017] In one embodiment of the present application, 0.01≤B≤0.8. By regulating the conductivity of the inner first pole piece within the above range, the current density of the inner pole piece of the electrode assembly during the cycle is relatively large, which is beneficial to improving the cycle performance of the secondary battery.
[0018] In one embodiment of the present application, the thickness of the first current collector of the single-sided first pole sheet is T1μm, and the thickness of the first current collector of the inner first pole sheet is T2μm, and T1≥T2. In one embodiment of the present application, the first pole sheet is a positive pole sheet, 12≤T1≤25, 6≤T2≤16. In one embodiment of the present application, the first pole sheet is a negative pole sheet, 14≤T1≤25, 4≤T2≤16. The above-mentioned arrangement is conducive to improving the problem of warping caused by uneven stress of the first current collector due to only one surface material layer being arranged on the first current collector of the single-sided first pole sheet. At this time, a double-layer material layer is arranged on the outer single-sided first pole sheet of the electrode assembly, and the conductivity of the single-sided first pole sheet is made less than or equal to the conductivity of the inner first pole sheet. The effect of reducing the risk of black spots and lithium deposition on the outer pole sheet of the electrode assembly during the cycle is more obvious, and the secondary battery has good cycle performance.
[0019] In one embodiment of the present application, the shell is an aluminum-plastic film. When the aluminum-plastic film is selected as the shell, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.
[0020] In one embodiment of the present application, the first pole piece is a negative pole piece, the first material layer includes a first active material, the conductivity of the first active material is c S / cm, the second material layer includes a second active material, the conductivity of the second active material is d S / cm, c<d; the first active material and the second active material are independently selected from at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon or silicon-carbon composite. When the first pole piece is a negative pole piece, by setting a double-layer material layer on the outer pole piece of the electrode assembly, selecting the first active material and the second active material within the above-mentioned range, and regulating the conductivity of the first active material in the first material layer between the second material layer and the first current collector to be less than the conductivity of the second active material in the second material layer, it is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0021] In one embodiment of the present application, the shell is a steel shell. When a steel shell is selected as the shell, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.
[0022] The second aspect of the present application provides a method for preparing a secondary battery, which includes the following steps: preparing at least one single-sided first pole piece, at least one inner first pole piece, multiple second pole pieces, multiple separators, electrolytes and shells, and assembling to obtain a secondary battery; wherein, the method for preparing the single-sided first pole piece includes the following steps: sequentially arranging a first material layer and a second material layer on the second surface of the first current collector to obtain a single-sided first pole piece; the method for preparing the inner first pole piece includes the following steps: arranging a first active material layer on both the first surface and the second surface of the first current collector to obtain an inner first pole piece. The above-mentioned preparation method is used to prepare a secondary battery, which is conducive to process operation and production. The obtained secondary battery has a low risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, and the secondary battery has good cycle performance.
[0023] In one embodiment of the present application, the first material layer includes a first active material, the conductivity of the first active material is a S / cm, the second material layer includes a second active material, the conductivity of the second active material is b S / cm, and a < b. Compared with the outer pole piece of a conventional electrode assembly, the impedance of the outer pole piece of the electrode assembly is increased, thereby slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is conducive to reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0024] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. The secondary battery in the present application has good cycle performance, so the electronic device in the present application has a long service life.
[0025] Beneficial effects of the embodiments of the present application:
[0026] The present application provides a secondary battery, a method for preparing a secondary battery, and an electronic device. A double-layer material layer is arranged on a single-sided outer first pole piece of an electrode assembly, and the conductivity of the single-sided outer first pole piece is made less than or equal to the conductivity of the inner first pole piece. At this time, the current density at the outermost side of the electrode assembly is reduced, the consumption rate of the electrolyte during the cycle is reduced, the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is reduced, and the cycle performance of the secondary battery is improved.
[0027] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0029] Figure 1 A schematic diagram of a cross-sectional structure of a secondary battery according to an embodiment of the present application observed along its length direction;
[0030] Figure 2 for Figure 1 Another schematic cross-sectional structure diagram of a secondary battery observed along its length direction.
[0031] Figure numerals: secondary battery 001; electrode assembly 01; shell 02; first pole piece 10; outer first pole piece 101; inner first pole piece 102; first current collector 11; first active material layer 12; first material layer 121; second material layer 122; third material layer 123; second pole piece 20; second current collector 21; second active material layer 22; first pole ear assembly 13; first pole ear 131; second pole ear assembly 23; second pole ear 231; diaphragm 30. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0033] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0034] The first aspect of the present application provides a secondary battery, including an electrolyte, a shell and an electrode assembly of a laminate structure, along the thickness direction of the electrode assembly, the electrode assembly includes a first pole sheet, a second pole sheet and a diaphragm arranged between the first pole sheet and the second pole sheet; the electrode assembly also includes a first pole tab assembly and a second pole tab assembly, the first pole tab assembly includes a plurality of first pole tabs, the second pole tab assembly includes a plurality of second pole tabs, the plurality of first pole tabs correspond one-to-one to the first pole sheet, and the plurality of second pole tabs correspond one-to-one to the second pole sheet. The first pole piece includes two outer first pole pieces and at least one inner first pole piece. Along the thickness direction of the electrode assembly, the two outer first pole pieces are respectively located at the outermost two sides of the electrode assembly, and the inner first pole piece is located between the two outer first pole pieces; the first pole piece includes a first current collector and a first active material layer. The first current collector includes a first surface and a second surface arranged opposite to each other along the thickness direction of the electrode assembly. The first surface is closer to the shell than the second surface. The first surface and the second surface of the inner first pole piece are both provided with a first active material layer; at least one outer first pole piece is a single-sided first pole piece. The first surface of the single-sided first pole piece is not provided with a first active material layer, and the second surface of the single-sided first pole piece is provided with a first active material layer. The first active material layer arranged on the second surface of the single-sided first pole piece is composed of a first material layer and a second material layer arranged in a stacked manner, and the first material layer is located between the first current collector and the second material layer. The conductivity of the single-sided first pole piece is AS / cm, and the conductivity of the inner first pole piece is BS / cm, and A≤B.
[0035] In this application, the electrode assembly of the laminated structure is defined as having a width direction of X, a length direction of Y, and a thickness direction of Z. It is understood that the length direction, width direction, and thickness direction of the first electrode sheet, the second electrode sheet, and the diaphragm are the same as those of the electrode assembly. For example, Figure 1 and Figure 2As shown, the secondary battery 001 includes an electrode assembly 01 and a shell 02 of a laminated structure. Along the thickness direction Z direction of the electrode assembly 01, the electrode assembly 01 includes a first pole sheet 10 and a second pole sheet 20 which are stacked and a diaphragm 30 arranged between the first pole sheet 10 and the second pole sheet 20; the electrode assembly 01 also includes a first pole ear assembly 13 and a second pole ear assembly 23, the first pole ear assembly 13 includes a plurality of first pole ears 131, the second pole ear assembly 23 includes a plurality of second pole ears 231, the plurality of first pole ears 131 correspond one-to-one to the first pole sheet 10, and the plurality of second pole ears 231 correspond one-to-one to the second pole sheet 20. The first pole piece 10 includes two outer first pole pieces 101 and an inner first pole piece 102. Along the thickness direction Z direction of the electrode assembly 01, the two outer first pole pieces 101 are respectively located on the outermost sides of the electrode assembly 01, and the inner first pole piece 102 is located between the two outer first pole pieces 101; the first pole piece 10 includes a first current collector 11 and a first active material layer 12. The first current collector 11 includes a first surface (not shown in the figure) and a second surface (not shown in the figure) arranged opposite to each other along the thickness direction Z direction of the electrode assembly 01. The first surface is closer to the second surface than the second surface. The shell 02, the first surface and the second surface of the inner first pole piece 102 are both provided with a first active material layer 12; the two outer first pole pieces 101 are single-sided first pole pieces 10, the first surface of the single-sided first pole piece 10 is not provided with the first active material layer 12, and the second surface of the single-sided first pole piece 10 is provided with a first active material layer 12, and the first active material layer 12 arranged on the second surface of the single-sided first pole piece 10 is composed of a first material layer 121 and a second material layer 122 that are stacked, and the first material layer 121 is located between the first current collector 11 and the second material layer 122.
[0036] The inventors have found that by adding a material layer between the active material layer and the current collector of the single-sided outer electrode sheet of the electrode assembly, that is, adding a second material layer between the first current collector and the second material layer, the self-impedance of the single-sided outer electrode sheet is increased, so that the conductivity of the first single-sided outer electrode sheet of the electrode assembly is greater than or equal to the conductivity of the first inner electrode sheet, that is, A≤B, and the current density of the outer electrode sheet of the electrode assembly is reduced, slowing down the consumption rate of the electrolyte in the outer electrode sheet of the electrode assembly during the cycle, thereby reducing the risk of black spots and lithium precipitation in the outer electrode sheet of the electrode assembly, and improving the cycle performance of the secondary battery. When the current density of the outer electrode sheet of the electrode assembly is greater than the current density of the inner electrode sheet, that is, A>B, the electrolyte consumption rate in the outer electrode sheet of the electrode assembly is too fast, and black spots or lithium precipitation problems are likely to occur in the outer electrode sheet of the electrode assembly, reducing the cycle performance and safety performance of the secondary battery. Therefore, by setting a double-layer material layer on the single-sided outer electrode sheet of the electrode assembly, and making the conductivity of the outer single-sided first electrode sheet less than or equal to the conductivity of the inner first electrode sheet, the current density of the outer electrode sheet of the electrode assembly is reduced, thereby reducing the consumption rate of the electrolyte during the cycle, reducing the risk of black spots and lithium deposition on the outer electrode sheet of the electrode assembly during the cycle, and improving the cycle performance of the secondary battery.
[0037] It should be noted that the first active material layer of the present application can be provided on the entire surface area of the first current collector or on a partial surface area of the first current collector. The present application has no particular limitation as long as the purpose of the present application can be achieved.
[0038] In one embodiment of the present application, 0.3≤A / B≤1. For example, the value of A / B can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or a range consisting of any two of these values. By regulating the value of A / B within the above range, the current density of the outer electrode sheet of the electrode assembly is greater than or equal to the current density of the inner electrode sheet, and the consumption rate of the electrolyte during the cycle is slowed down, which is conducive to reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0039] In one embodiment of the present application, 0.65≤A / B≤1. For example, the value of A / B can be 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1 or a range consisting of any two of these values. By regulating the value of A / B within the above range, the current density of the outer pole piece of the electrode assembly is greater than or equal to the current density of the inner pole piece, and the consumption rate of the electrolyte during the cycle is slowed down, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0040] In one embodiment of the present application, the first pole piece is a positive pole piece. When the positive pole piece is selected as the first pole piece, the first pole piece on the outside of the electrode assembly is the positive pole piece, which further slows down the consumption rate of the electrolyte on the outside of the electrode assembly during the cycle, and has a more obvious effect of reducing the risk of black spots and lithium deposition on the pole piece on the outside of the electrode assembly during the cycle, thereby further improving the cycle performance of the secondary battery.
[0041] In one embodiment of the present application, the first material layer includes a first active material, the first active material includes at least one of lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP) or lithium manganese oxide (LiMn2O4), and the second material layer includes a second active material, the second active material includes at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), nickel cobalt manganese ternary material or lithium-rich manganese-based material. Suitable first active materials and second active materials are selected within the above-mentioned range of types so that the conductivity of the first active material and the second active material is within a suitable range, and compared with the outer electrode sheet of a conventional electrode assembly, the impedance of the outer electrode sheet of the electrode assembly is increased, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, and helping to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery. In the present application, nickel-cobalt-manganese ternary materials include but are not limited to LiNi 0.90 Co 0.05 Mn 0.05 At least one of NCM955, NCM811, NCM622, NCM523 or NCM111. The lithium-rich manganese-based material is a composite positive electrode material Li2MnO3·LiMO2 based on Li2MnO3, wherein M is a binary or ternary layered material of Ni, Co, Mn or Ni, Co, Mn.
[0042] In one embodiment of the present application, the Dv50 of the first active material is 3μm to 25μm, for example, the Dv50 of the first active material can be 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm or a range consisting of any two of the values; the Dv99 of the first active material is 10μm to 65μm, for example, the Dv99 of the first active material can be 10μm, 13μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm, 50μm, 52μm, 55μm, 58μm, 60μm , 62μm, 65μm or a range consisting of any two of the values therein; the Dv50 of the second active material is 4.5μm to 24.5μm, for example, the Dv50 of the second active material may be 4.5μm, 4.8μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 23μm, 24μm, 24.2μm, 24.5μm or a range consisting of any two of the values therein; the Dv99 of the second active material is 45μm to 65μm, for example, the Dv99 of the second active material may be 45μm, 48μm, 50μm, 52μm, 55μm, 58μm, 60μm, 62μm, 65μm or a range consisting of any two of the values therein. By regulating the Dv50 and Dv99 of the first active material and the Dv50 and Dv99 of the second active material within the above range, the conductivity of the first active material and the second active material is within a suitable range, which is beneficial to further increase the impedance of the first material layer and the second material layer, thereby increasing the impedance of the outer electrode sheet of the electrode assembly, reducing the conductivity of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, and helping to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0043] In the present application, Dv50 refers to the particle size that reaches 50% of the volume accumulation in the volume-based particle size distribution of the active material, measured from the small particle size; Dv99 refers to the particle size that reaches 99% of the volume accumulation in the volume-based particle size distribution of the active material, measured from the small particle size. The present application has no particular restrictions on the regulation method of Dv50 and Dv99 of the active material, as long as the purpose of the present application can be achieved. For example, the Dv50 and Dv99 of the active material can be regulated by grading and grinding the particles of the active material. Exemplarily, when other conditions remain unchanged, the Dv50 and Dv99 of the active material are reduced by extending the grinding time; the Dv50 and Dv99 of the active material are increased by shortening the grinding time.
[0044] In one embodiment of the present application, the first material layer includes a first binder, and the second material layer includes a second binder. The first binder and the second binder are independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid. Based on the mass of the first material layer, the mass percentage W1 of the first binder is 0.5% to 5%. For example, the mass percentage W1 of the first binder can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range consisting of any two of the values; based on The mass of the second material layer, the mass percentage content W2 of the second binder is 0.4% to 5%, for example, the mass percentage content W2 of the second binder can be 0.4%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range consisting of any two values. By selecting the first binder and the second binder within the above-mentioned range, and regulating the mass percentage content of the first binder and the mass percentage content of the second binder within the above-mentioned range, it is beneficial to increase the impedance of the outer electrode sheet of the electrode assembly and reduce the conductivity of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0045] In one embodiment of the present application, the first material layer includes a first conductive agent, and the second material layer includes a second conductive agent, and the first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, carbon nanotubes, graphene or conductive graphite; based on the mass of the first material layer, the mass percentage W'1 of the first conductive agent is 1% to 10%, for example, the mass percentage of the first conductive agent W'1 can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the values; based on the mass of the second material layer, the mass percentage W'2 of the second conductive agent is 1% to 10%, for example, the mass percentage W'2 of the second conductive agent can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the values. By selecting the first conductive agent and the second conductive agent within the above-mentioned range, and regulating the mass percentage of the first conductive agent and the mass percentage of the second conductive agent within the above-mentioned range, it is beneficial to increase the impedance of the outer electrode sheet of the electrode assembly and reduce the conductivity of the outer electrode sheet of the electrode assembly, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, and reducing the risk of black spots and lithium deposition on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0046] In one embodiment of the present application, based on the mass of the first material layer, the mass percentage W"1 of the first active material is 85% to 98.5%; and / or, based on the mass of the second material layer, the mass percentage W"2 of the second active material is 85% to 98.6%. For example, the mass percentage content W"1 of the first active material can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 98.3%, 98.5% or a range consisting of any two of the values therein; the mass percentage content W"2 of the second active material can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 98.2%, 98.4%, 98.5%, 98.6% or a range consisting of any two of the values therein. By regulating the mass percentage of the first active material and / or the mass percentage of the second active material within the above range, it is beneficial to increase the impedance of the outer electrode plate of the electrode assembly, thereby slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, which is beneficial to reducing the risk of black spots and lithium deposition on the outer electrode plate of the electrode assembly during the cycle, and at the same time the secondary battery has good cycle performance.
[0047] In one embodiment of the present application, Figure 1 and Figure 2As shown, the first active material layer 12 disposed on the first surface and the second surface of the inner first pole piece 102 is a third material layer 123. The third material layer includes a third active material, and the third active material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material or lithium-rich manganese-based material. Based on the mass of the third material layer, the mass percentage content W"3 of the third active material is 85% to 98.6%. For example, the mass percentage content W"3 of the third active material can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 98.2%, 98.5%, 98.6% or a range consisting of any two of the values. By selecting the third active material of the above type and regulating the mass percentage of the third active material within the above range, the inner electrode sheet of the electrode assembly has a higher conductivity, which is beneficial to shortening the conductivity difference between the inner and outer electrode sheets of the electrode assembly. While the inner electrode sheet of the electrode assembly has a higher conductivity, the conductivity of the outer electrode sheet of the electrode assembly is relatively low, thereby slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, which is beneficial to reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, and the secondary battery has good cycle performance.
[0048] In one embodiment of the present application, Figure 1 and Figure 2 As shown, the thickness H1 of the first material layer 121 is 20 μm to 60 μm, and the thickness H2 of the second material layer 122 is 20 μm to 150 μm. For example, the thickness H1 of the first material layer can be 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 52 μm, 55 μm, 58 μm, 60 μm, or a range consisting of any two of these values; the thickness H2 of the second material layer can be 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 52 μm, 55 μm, 58 μm, 60 μm, or a range consisting of any two of these values. 5μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm or a range consisting of any two of these values. By regulating the thickness of the first material layer and the thickness of the second material layer within the above range, it is beneficial to increase the impedance of the outer electrode sheet of the electrode assembly, thereby slowing down the consumption rate of the electrolyte on the outer side of the electrode assembly during the cycle, which is beneficial to reduce the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, while taking into account the high energy density of the secondary battery, the cycle performance of the secondary battery is improved.
[0049] In one embodiment of the present application, Figure 1 and Figure 2 As shown, the thickness H3 of the third material layer 123 is 80 μm to 250 μm. For example, the thickness H3 of the third material layer can be 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm, 245μm, 250μm or a range consisting of any two of the values. By regulating the thickness of the third material layer within the above range, the secondary battery has a higher energy density, and at the same time, the inner electrode sheet of the electrode assembly has a higher conductivity. The difference in conductivity between the inner and outer electrode sheets of the electrode assembly is small, which is beneficial to slowing down the consumption rate of the electrolyte on the outside of the electrode assembly during the cycle, and reducing the risk of black spots and lithium deposition on the outer electrode sheets of the electrode assembly during the cycle. The secondary battery has a higher energy density and good cycle performance.
[0050] In the present application, the thickness of the material layer can be controlled by means known to those skilled in the art. For example, when the slurry is coated on the surface of the current collector, on the basis of a certain solid content of the slurry, the thickness of the material layer can be increased by increasing the coating weight, and the thickness of the material layer can be reduced by reducing the coating weight; the thickness of the material layer can also be reduced by increasing the cold pressing pressure when the electrode is cold pressed, and the thickness of the material layer can be increased by reducing the cold pressing pressure.
[0051] In one embodiment of the present application, 0.01≤B≤0.8. For example, the value of B can be 0.01, 0.012, 0.015, 0.018, 0.02, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or a range consisting of any two of these values. By regulating the conductivity of the inner first pole piece within the above range, the current density of the outer pole piece of the electrode assembly during the cycle is small, which is beneficial to improving the cycle performance of the secondary battery.
[0052] In one embodiment of the present application, the thickness of the first current collector of the single-sided first pole piece is T1 μm, the thickness of the first current collector of the inner first pole piece is T2 μm, and T1 ≥ T2. In one embodiment of the present application, the first pole piece is a positive pole piece, 12 ≤ T1 ≤ 25, 6 ≤ T2 ≤ 16; for example, the value of T1 can be 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or a range consisting of any two of the values, and the value of T2 can be 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or a range consisting of any two of the values. In one embodiment of the present application, the first pole piece is a negative pole piece, 14≤T1≤25, 4≤T2≤16; for example, the value of T1 can be 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or a range consisting of any two of the values, and the value of T2 can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or a range consisting of any two of the values. Through the above arrangement, it is beneficial to improve the problem of warping caused by uneven stress of the first current collector caused by only one surface material layer on the first current collector of the single-sided first pole piece. At this time, a double-layer material layer is arranged on the outer single-sided first pole piece of the electrode assembly, and the conductivity of the single-sided first pole piece is made less than or equal to the conductivity of the inner first pole piece. The effect of reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle is more obvious, and the secondary battery has good cycle performance.
[0053] In one embodiment of the present application, the shell is an aluminum-plastic film. When the aluminum-plastic film is used as the shell and the first pole piece on the outer side of the electrode assembly is used as the positive pole piece, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.
[0054] In the present application, when the first electrode sheet or the second electrode sheet is a positive electrode sheet, the present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0055] In one embodiment of the present application, the first electrode sheet is a negative electrode sheet, the first material layer includes a first active material, the conductivity of the first active material is c S / cm, the second material layer includes a second active material, the conductivity of the second active material is d S / cm, c<d; the first active material and the second active material are independently selected from at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon or silicon-carbon composite. When the first electrode sheet is a negative electrode sheet, by setting a double-layer material layer on the outer electrode sheet of the electrode assembly, the first active material and the second active material are selected within the above-mentioned type range, so that the conductivity of the first active material and the second active material is within a suitable range, compared with the outer electrode sheet of the conventional electrode assembly, the impedance of the outer electrode sheet of the electrode assembly is increased, thereby reducing the current density of the outer electrode sheet of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is conducive to reducing the risk of black spots and lithium precipitation on the outer electrode sheet of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0056] In one embodiment of the present application, the shell is a steel shell. When the steel shell is selected as the shell and the first pole piece on the outer side of the electrode assembly is used as the negative pole piece, it is beneficial to reduce the risk of short circuit of the secondary battery and improve the cycle performance and safety performance of the secondary battery.
[0057] In one embodiment of the present application, the first active material layer disposed on the first surface and the second surface of the inner first pole piece is a third material layer, the third material layer includes a third active material, and the third active material includes at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon or silicon-carbon composites. Figure 1 and Figure 2 As shown, the first active material layer 12 disposed on the first surface and the second surface of the inner first pole piece 102 is a third material layer 123. By selecting the third active material of the above type, the inner pole piece of the electrode assembly has a higher conductivity, which is conducive to shortening the conductivity difference between the inner and outer pole pieces of the electrode assembly. While the inner pole piece of the electrode assembly has a higher conductivity, the conductivity of the outer pole piece of the electrode assembly is relatively low, thereby slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is conducive to reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, and the secondary battery has good cycle performance.
[0058] In the present application, when the first pole piece or the second pole piece is a negative pole piece, the present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as lithium copper composite current collector, carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.). In this case, the first material layer, the second material layer and the third material layer are all negative electrode material layers. The first material layer also includes a first conductive agent and a first binder, the second material layer also includes a second conductive agent and a second binder, and the third material layer also includes a third conductive agent and a third binder. The first conductive agent, the second conductive agent, and the third conductive agent can be independently selected from at least one of conductive carbon black, carbon nanotubes, graphene, or conductive graphite, and the first binder, the second binder, and the third binder can be independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylic acid salt, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion, or polyacrylic acid. In the present application, when the first electrode is a negative electrode, the mass ratio of the first active material, the first conductive agent, and the first binder; the mass ratio of the second active material, the second conductive agent, and the second binder; and the mass ratio of the third active material, the third conductive agent, and the third binder can be adjusted by those skilled in the art according to actual needs, as long as the purpose of the present application can be met.
[0059] The second aspect of the present application provides a method for preparing a secondary battery, which includes the following steps: preparing at least one single-sided first pole piece, at least one inner first pole piece, multiple second pole pieces, multiple separators, electrolytes and shells, and assembling to obtain a secondary battery; wherein, the method for preparing the single-sided first pole piece includes the following steps: sequentially arranging a first material layer and a second material layer on the second surface of the first current collector to obtain a single-sided first pole piece; the method for preparing the inner first pole piece includes the following steps: arranging a first active material layer on both the first surface and the second surface of the first current collector to obtain an inner first pole piece. The above-mentioned preparation method is used to prepare a secondary battery, which is conducive to process operation and production. The obtained secondary battery has a low risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, and the secondary battery has good cycle performance.
[0060] The present application has no particular restrictions on the manner of setting the first material layer and the second material layer on the second surface of the first current collector, as long as the purpose of the present application can be achieved. For example, the first active material, the first binder, and the first conductive agent are mixed in a certain mass ratio and added to a solvent to prepare a first material layer slurry, and the first material layer slurry is applied on the second surface of the first current collector, and after drying, a first pole piece coated with the first material layer is obtained; the second active material, the second binder, and the second conductive agent are mixed in a certain mass ratio and added to a solvent to prepare a second material layer slurry, and the second material layer slurry is applied on the surface of the first material layer away from the first current collector, and after drying, a single-sided outer first pole piece coated with the first material layer and the second material layer is obtained. The present application has no particular restrictions on the manner of obtaining the single-sided first pole piece, as long as the purpose of the present application can be achieved. For example, the single-sided outer first pole piece coated with the first material layer and the second material layer is cold pressed, cut, and welded to the first pole ear, so as to obtain a single-sided first pole piece. The present application has no particular restrictions on the solvents and solid content used in the above-mentioned first material layer slurry and second material layer slurry, as long as the purpose of the present application can be achieved. The present application does not have any particular restrictions on the temperature and time of the above-mentioned drying. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application does not have any particular restrictions on the process parameters of the above-mentioned cold pressing, cutting and welding of the first pole ear. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application does not have any particular restrictions on the size of the above-mentioned first material layer and second material layer, as long as the purpose of the present application can be achieved.
[0061] In the present application, the mass percentage of the first active material, the first binder and the first conductive agent can be controlled by controlling the mass ratio of the first active material, the first binder and the first conductive agent in the first material layer slurry; the mass percentage of the second active material, the second binder and the second conductive agent can be controlled by controlling the mass ratio of the second active material, the second binder and the second conductive agent in the second material layer slurry.
[0062] The present application has no particular restrictions on the manner of setting the first active material layer on both the first surface and the second surface of the first current collector, that is, setting the third material layer on both surfaces of the first current collector, as long as the purpose of the present application can be achieved. For example, the third active material, the third binder and the third conductive agent are mixed in a certain mass ratio and then added to a solvent to prepare a third material layer slurry; the third material layer slurry is coated on the first surface of the first current collector, and after drying, a single-sided inner first pole piece coated with the third material layer is obtained; the above steps are repeated on the other surface of the first current collector to obtain a double-sided inner first pole piece coated with the third material layer. The present application has no particular restrictions on the manner of obtaining the inner first pole piece, as long as the purpose of the present application can be achieved. For example, the double-sided inner first pole piece coated with the third material layer is cold pressed, cut, and welded to the first pole ear to obtain the inner first pole piece. The present application has no particular restrictions on the solvent and solid content used in the above-mentioned third material layer slurry, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the temperature and time of the above-mentioned drying, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the process parameters of the cold pressing, cutting and welding of the first pole ear, and those skilled in the art can select them according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the size of the third material layer, as long as the purpose of the present application can be achieved.
[0063] In the present application, the mass percentages of the third active material, the third binder and the third conductive agent may be regulated by regulating the mass ratio of the third active material, the third binder and the third conductive agent.
[0064] The present application does not particularly limit the assembly method of the secondary battery, as long as the purpose of the present application can be achieved. For example, the outer first pole piece, the diaphragm, the second pole piece, the diaphragm, the inner first pole piece, the diaphragm, the second pole piece, the diaphragm, and the outer first pole piece are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly of the stacked structure, the electrode assembly is placed in a housing, and the electrolyte is injected into the housing and sealed to obtain a secondary battery.
[0065] In one embodiment of the present application, the first material layer includes a first active material, the conductivity of the first active material is a S / cm, the second material layer includes a second active material, the conductivity of the second active material is b S / cm, and a<b. By arranging a double-layer material layer on the outer pole piece of the electrode assembly, and regulating the conductivity of the first active material in the first material layer between the second material layer and the first current collector to be less than the conductivity of the second active material in the second material layer, compared with the outer pole piece of the conventional electrode assembly, the impedance of the outer pole piece of the electrode assembly is increased, thereby reducing the current density of the outer pole piece of the electrode assembly, slowing down the consumption rate of the electrolyte outside the electrode assembly during the cycle, which is conducive to reducing the risk of black spots and lithium precipitation on the outer pole piece of the electrode assembly during the cycle, thereby improving the cycle performance of the secondary battery.
[0066] In the present application, the conductivity of the outer first pole piece can be regulated by regulating the conductivity of the first active material and the second active material. Further, the conductivity of the outer first pole piece can be regulated by regulating the type and particle size of the first active material and the type and particle size of the second active material. For example, for the same type of active material, when the particle size of the active material particles is small, that is, Dv50 and Dv99 are small, the conductivity of the active material is large. In the present application, the conductivity of the inner first pole piece can be regulated by regulating the type and mass percentage of the third active material. In the present application, the conductivity of the outer first pole piece and / or the inner first pole piece is also related to the overall thickness of the outer first pole piece and / or the inner first pole piece, the coating weight of the corresponding material layer, etc. For example, for the inner first pole piece of the same specification, when other conditions are the same, the thickness of the inner first pole piece is small and the coating weight is small, the conductivity of the inner first pole piece is large.
[0067] The electrolyte of the present application includes a lithium salt and a non-aqueous solvent. The lithium salt may include at least one of LiPF6, LiNO3, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) or lithium difluoroborate. The present application does not limit the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or ethyl methyl carbonate. The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate, propylene carbonate (PC), butylene carbonate or vinyl ethylene carbonate. Fluorinated carbonate compounds may include but are not limited to at least one of fluoroethylene carbonate, 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0068] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or at least one of aramid. The type of diaphragm may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes or spun membranes. The diaphragm of the present application may have a porous structure, and the present application has no particular restrictions on the size of the pore size of the porous structure of the diaphragm, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01 μm to 1 μm. The present application has no particular restrictions on the thickness of the diaphragm, as long as the purpose of the present application can be achieved. For example, the thickness of the diaphragm can be 5 μm to 40 μm.
[0069] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one or more embodiments, the secondary battery may include, but is not limited to, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0070] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. The secondary battery in the present application has good cycle performance, so the electronic device in the present application has a long service life.
[0071] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0072] Example
[0073] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0074] Test methods and equipment:
[0075] Conductivity test of the electrode:
[0076] The lithium-ion battery discharged at 0.2C to 3.0V was disassembled, and the outer first pole piece of the electrode assembly was taken out. According to the arrangement of the pole pieces in the electrode assembly, the inner first pole piece of the electrode assembly was taken out, and soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then, the outer first pole piece and the inner first pole piece were placed in an oven and baked at 80°C for 12 hours to obtain the treated outer first pole piece and inner first pole piece samples.
[0077] Use a resistivity tester (IEST, BER1200, Yuanneng Technology) to test the first outer electrode and the first inner electrode after treatment. Before use, reset the resistance and pressure of the resistance tester, place the electrode sample to be tested between the electrodes of the tester, take three different positions of the electrode with a cross-sectional area of 30mm×30mm on the sample for testing, and measure the resistance values of the three electrode with a cross-sectional area of 30mm×30mm respectively. The average value is recorded as the resistance value of the electrode with a cross-sectional area of 30mm×30mm. And calculate according to the following formula:
[0078] R=ρ×l / s; γ=1 / ρ=l / Rs
[0079] Where R is the measured resistance value; ρ is the resistivity; l is the thickness of the measured electrode, s is the cross-sectional area, and γ is the measured conductivity of the electrode.
[0080] The conductivity A of the outer first pole piece and the conductivity B of the inner first pole piece are obtained respectively.
[0081] Conductivity test of active materials:
[0082] 1.5 g of the first active material powder sample was weighed and made into a cylindrical sheet with a diameter of 10 mm and a thickness of 2 mm using a circular abrasive tool under a pressure of 80 MPa. The treated cylindrical sheet was measured using a powder resistivity & compaction density meter (IEST, PRCD3100, Yuanneng Technology). The conductivity was calculated using the following formula:
[0083] ρ=2πlU / I;γ=1 / ρ
[0084] Wherein, ρ is the resistivity; l is the probe coefficient of the instrument used, U is the DC voltage value measured by the two inner electrodes of the instrument used, I is the DC current value applied by the two outer electrodes of the instrument used, and γ is the measured conductivity of the active material.
[0085] The electrical conductivity a of the first active material and the electrical conductivity b of the second active material are obtained respectively.
[0086] Particle size test:
[0087] The lithium-ion battery discharged at 0.2C to 3.0V was disassembled, and the outer first pole piece of the electrode assembly was taken out, and it was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in sequence. Then, the outer first pole piece was placed in an oven and baked at 80°C for 12 hours to obtain the treated outer first pole piece sample.
[0088] The cross section of the first outer pole piece was observed using a scanning electron microscope, and a relatively clear double-layer coating boundary line was observed. The second material layer was scraped off along the double-layer coating boundary line with a scraper, and washed with dimethyl carbonate (DMC) to obtain a second active material powder sample. The particles of the second active material were added to a 50mL clean beaker, and 20mL of deionized water was added. A 120W ultrasonic cleaner was used for ultrasonic cleaning for 5 minutes to completely disperse the particles of the second active material in the deionized water to obtain a sample dispersion. The above sample dispersion was tested using a particle size analyzer (model: MasterSizer 2000) to obtain the particle sizes of the second active material Dv50 and Dv99.
[0089] The first material layer was scraped off with a scraper and washed with dimethyl carbonate (DMC) to obtain a first active material powder sample. The particles of the first active material were added to a 50 mL clean beaker, and 20 mL of deionized water was added. A 120 W ultrasonic cleaner was used for ultrasonic cleaning for 5 min to completely disperse the particles of the first active material in the deionized water to obtain a sample dispersion. The sample dispersion was tested using a particle size analyzer (model: MasterSizer 2000) to obtain the particle sizes Dv50 and Dv99 of the first active material.
[0090] Material layer thickness test:
[0091] The lithium-ion battery discharged at 0.2C to 3.0V was disassembled, and the outer first pole piece and the inner first pole piece of the electrode assembly were taken out, and they were soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then, the outer first pole piece and the inner first pole piece were placed in an oven and baked at 80°C for 12 hours to obtain the treated outer first pole piece samples and inner first pole piece samples.
[0092] The outer first pole piece is subjected to argon ion polishing to obtain a cross section of the outer first pole piece. The morphology of the cross section of the outer first pole piece along the thickness direction is observed by a field emission scanning electron microscope (Philips, model XL-30) and a scanning electron microscope photograph is taken. The thickness H1 of the first material layer and the thickness H2 of the second material layer are measured by the scanning electron microscope.
[0093] The inner first pole piece is subjected to argon ion polishing to obtain the cross section of the outer first pole piece. The cross-sectional morphology of the inner first pole piece along the thickness direction is observed by a field emission scanning electron microscope (Philips, XL-30 model) and scanning electron microscope photographs are taken. The thickness H3 of the third material layer is measured by scanning electron microscope.
[0094] Lithium deposition performance test:
[0095] The lithium-ion battery in the embodiment and the comparative example is placed in a thermostat at 10°C. After 60 minutes, it is charged to 4.5V at 2C constant current, charged to 0.05C at 4.5V constant voltage, and left to stand for 5 minutes. Then, it is discharged to 3.0V at 0.5C constant current. This is one cycle. After 100 cycles of the above charge and discharge process, it is charged to 4.5V at 2C constant current, charged to 0.05C at 4.5V constant voltage, and left to stand for 5 minutes. After that, the lithium-ion battery is disassembled, the outer pole piece of the electrode assembly is taken out, and the lithium deposition state on the surface of the outer pole piece is observed. The non-lithium deposition area on the outer pole piece surface is golden yellow, and the lithium deposition area is grayish white.
[0096] The criteria for judging the degree of lithium deposition in lithium-ion batteries are as follows: a lithium deposition area of 0% means no lithium deposition, i.e., the degree of lithium deposition is zero; a lithium deposition area greater than 0 and less than or equal to 2% means mild lithium deposition, i.e., the degree of lithium deposition is mild; a lithium deposition area greater than 2% and less than or equal to 20% means moderate lithium deposition, i.e., the degree of lithium deposition is moderate; a lithium deposition area greater than 20% and less than or equal to 100% means severe lithium deposition, i.e., the degree of lithium deposition is severe, wherein the percentage of the lithium deposition area is calculated based on the total area of the first active material layer of the outer first electrode.
[0097] Black spot test:
[0098] Place the lithium-ion battery in a 0℃ constant temperature box and let it stand for 60 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at 0℃ with a constant current of 1C to a full charge voltage of 4.5V, then charge it to 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and then discharge it to 3.0V at a constant current of 1C; this is a charge and discharge cycle. After 500 cycles of charge and discharge, charge it to a full charge voltage of 4.5V at a constant current of 1C, and then charge it to 0.025C at a constant voltage of 4.5V to obtain a fully charged battery with 500 cycles. Disassemble the lithium-ion battery in a dry room with a humidity of less than 5%, and take photos to record whether there are black spots on the surface of the outer pole piece.
[0099] The criteria for judging the degree of black spots in lithium-ion batteries are as follows: a black spot area of 0% means no black spots appear, a black spot area less than or equal to 2% means mild black spots, a black spot area of 2% to 20% means moderate black spots, and a black spot area greater than 20% means severe black spots, where the percentage of the black spot area is calculated based on the total area of the first active material layer of the outer first pole piece.
[0100] Cycle performance test:
[0101] Place the lithium-ion battery in a 25℃ constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25℃. Charge to 4.5V at 1C constant current, charge to 0.025C at 4.5V constant voltage, let stand for 5 minutes, and discharge to 3.0V at 0.2C constant current. This is the first cycle, and the initial discharge capacity is recorded as C0. Perform charge and discharge cycles on the lithium-ion battery according to the above process. When the cycle reaches 400 cycles (cls), stop the test and record the discharge capacity after 400 cycles (cls) as C1. Calculate the 400cls capacity retention rate as an indicator for evaluating the cycle performance of lithium-ion batteries.
[0102] 400cls capacity retention rate (%) = C1 / C0×100%.
[0103] The higher the 400cls capacity retention rate, the better the cycle performance of the lithium-ion battery.
[0104] Example 1-1
[0105] <Preparation of the first pole piece>
[0106] A positive electrode plate is selected as the first electrode plate, and the first active material lithium iron phosphate (LFP, Dv50=5μm, Dv99=30μm), the first binder polyvinylidene fluoride, and the first conductive agent conductive carbon black are mixed in a mass ratio of 92:3:5, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a first material layer slurry with a solid content of 70wt%; the second active material lithium manganese oxide (LiMn2O4, Dv50=8μm, Dv99=50μm), the second binder polyvinylidene fluoride, and the second conductive agent conductive carbon black are mixed in a mass ratio of 92:3:5, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a second material layer slurry with a solid content of 70wt%. The first material layer slurry is coated on one surface of the positive electrode current collector aluminum foil with a thickness of 14 μm, and baked at 120°C for 1 hour to obtain a positive electrode sheet coated with the first material layer. The second material layer slurry is coated on the surface of the first material layer away from the positive electrode current collector aluminum foil, and baked at 120°C for 1 hour to obtain a single-sided outer positive electrode sheet coated with the first material layer and the second material layer. After cold pressing, cutting, and welding the positive electrode ears, an outer positive electrode sheet with a specification of 50 mm×90 mm is obtained. Among them, the coating weight of the first material layer is 6.5 mg / mm 2 The thickness of the first material layer is 40 μm. Based on the mass of the first material layer, the mass percentage content W1 of the first binder is 3%, and the mass percentage content W'1 of the first conductive agent is 5%. The coating weight of the second material layer is 13 mg / mm 2The thickness of the second material layer is 80 μm. Based on the mass of the second material layer, the mass percentage content W2 of the second binder is 3%, and the mass percentage content W′2 of the second conductive agent is 5%.
[0107] The third active material lithium manganate (LiMn2O4, Dv50 = 8μm, Dv99 = 50μm), the third binder polyvinylidene fluoride, and the third conductive agent conductive carbon black are mixed in a mass ratio of 92:3:5 and added to N-methylpyrrolidone (NMP), and stirred evenly under the action of a vacuum mixer to obtain a third material layer slurry with a solid content of 70wt%. The third material layer slurry is coated on one surface of a positive electrode collector aluminum foil with a thickness of 14μm, and baked at 120°C for 1 hour to obtain a positive electrode sheet coated with the third material layer. The above steps are repeated on the other surface of the positive electrode collector aluminum foil to obtain a positive electrode sheet coated with the third material layer on both sides. Then, after drying under vacuum conditions at 120°C for 1 hour, the inner positive electrode sheet with a specification of 50mm×90mm is obtained by cold pressing, cutting, and welding the positive electrode ears. Among them, the coating weight of the third material layer is 18mg / mm 2 The thickness of the third material layer is 160 μm, and based on the mass of the third material layer, the mass percentage content W"3 of the third active material is 92%.
[0108] <Preparation of the Second Pole Sheet>
[0109] A negative electrode sheet was selected as the second electrode sheet, and the negative electrode active material artificial graphite, conductive carbon black, and negative electrode binder styrene-butadiene rubber were mixed in a mass ratio of 94:2:4, deionized water was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 65wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and baked at 120°C for 1 hour to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The above steps were repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode material layer. After drying under vacuum conditions at 120°C for 1 hour, a negative electrode sheet with a specification of 50mm×90mm was obtained by cold pressing, cutting, and welding the negative electrode ears. Among them, the coating weight of the negative electrode material layer is 12mg / mm 2 , the thickness of the negative electrode material layer is 120μm.
[0110] <Preparation of Electrolyte>
[0111] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent; lithium salt LiPF6 is dissolved in the above organic solvent, and then fluoroethylene carbonate (FEC) is added and mixed evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of FEC is 5%, and the balance is the organic solvent.
[0112] <Diaphragm>
[0113] A polyethylene (PE) film with a thickness of 7 μm was used as the separator.
[0114] <Preparation of lithium-ion batteries>
[0115] The outer positive electrode sheet, separator, negative electrode sheet, separator, inner positive electrode sheet, separator, negative electrode sheet, separator, and outer positive electrode sheet prepared above are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly of the stacked structure, and the electrode assembly is placed in an aluminum plastic film, placed in an 80°C vacuum oven for 12 hours to remove moisture, and the prepared electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, formation, degassing, trimming and other processes. The design potential range of the lithium-ion battery is 3.0V to 4.5V.
[0116] Example 1-2 to Example 1-29
[0117] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. Among them, when the Dv50 and Dv99 of the same active material change, the grinding time is adjusted so that the Dv50 and Dv99 values are as shown in Table 1; when the thickness of the material layer changes, the coating weight is adjusted so that the thickness of the material layer is as shown in Table 1. When the type and / or Dv50 and Dv99 of the second active material change, the type and / or Dv50 and Dv99 of the third active material change accordingly.
[0118] Example 2-1
[0119] Except for preparing the positive electrode sheet, the negative electrode sheet and the lithium-ion battery according to the following steps and adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.
[0120] <Preparation of the first pole piece>
[0121] A negative electrode plate is selected as the first electrode plate, and the first active material artificial graphite, the first binder styrene butadiene rubber, and the first conductive agent conductive carbon black are mixed in a mass ratio of 92:3:5, and deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a first material layer slurry with a solid content of 65wt%; the second active material silicon-carbon composite SiC, the second binder styrene butadiene rubber, and the second conductive agent conductive carbon black are mixed in a mass ratio of 92:3:5, and deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a second material layer slurry with a solid content of 65wt%. The first material layer slurry is coated on one surface of the negative electrode current collector copper foil with a thickness of 12μm, and baked at 120℃ for 1 hour to obtain the negative electrode sheet coated with the first material layer. The second material layer slurry is coated on the surface of the first material layer away from the negative electrode current collector copper foil, and baked at 120℃ for 1 hour to obtain the single-sided outer negative electrode sheet coated with the first material layer and the second material layer. After cold pressing, cutting, and welding the negative electrode tab, the outer negative electrode sheet with a specification of 50mm×90mm is obtained. Among them, the coating weight of the first material layer is 4mg / mm 2 The thickness of the first material layer is 40 μm. Based on the mass of the first material layer, the mass percentage content W1 of the first binder is 3%, and the mass percentage content W'1 of the first conductive agent is 5%. The coating weight of the second material layer is 12 mg / mm 2 The thickness of the second material layer is 80 μm. Based on the mass of the second material layer, the mass percentage content W2 of the second binder is 3%, and the mass percentage content W′2 of the second conductive agent is 5%.
[0122] The third active material silicon-carbon composite SiC, the third binder styrene-butadiene rubber, and the third conductive agent conductive carbon black are mixed in a mass ratio of 92:3:5 and added to deionized water, and stirred evenly under the action of a vacuum mixer to obtain a third material layer slurry with a solid content of 65wt%. The third material layer slurry is coated on one surface of a negative electrode collector copper foil with a thickness of 12μm, and baked at 120°C for 1 hour to obtain a negative electrode sheet coated with the third material layer. The above steps are repeated on the other surface of the negative electrode collector copper foil to obtain a negative electrode sheet coated with the third material layer on both sides. Then, after drying under vacuum conditions at 120°C for 1 hour, the inner negative electrode sheet with a specification of 50mm×90mm is obtained by cold pressing, cutting, and welding the negative electrode ears. Among them, the coating weight of the third material layer is 14mg / mm 2 The thickness of the third material layer is 160 μm, and based on the mass of the third material layer, the mass percentage content W"3 of the third active material is 92%.
[0123] <Preparation of the Second Pole Sheet>
[0124] A positive electrode sheet was selected as the second electrode sheet, and the positive electrode active material lithium manganese oxide (LiMn2O4), the binder polyvinylidene fluoride, and the conductive agent conductive carbon black were mixed in a mass ratio of 92:3:5, and N-methylpyrrolidone (NMP) was added. The mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 14μm, and baked at 120°C for 1 hour to obtain a positive electrode sheet with a single-sided positive electrode material layer. The above steps were repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. After drying under vacuum conditions at 120°C for 1 hour, a positive electrode sheet with a specification of 50mm×90mm was obtained by cold pressing, cutting, and welding the positive electrode ears. Among them, the coating weight of the positive electrode material layer is 19mg / mm 2 , the thickness of the positive electrode material layer is 180μm.
[0125] <Preparation of lithium-ion batteries>
[0126] The outer negative electrode sheet, separator, positive electrode sheet, separator, inner negative electrode sheet, separator, positive electrode sheet, separator, and outer negative electrode sheet prepared above are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly of the stacked structure, and the electrode assembly is placed in a steel shell, placed in an 80°C vacuum oven for 12 hours to remove moisture, and the prepared electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, formation, degassing, trimming and other processes. The design potential range of the lithium-ion battery is 3.0V to 4.5V.
[0127] Example 2-2 to Example 2-4
[0128] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 2-1.
[0129] Comparative Example 1 and Comparative Example 2
[0130] Except that the first material layer is not provided on the outer positive electrode plate, but only the second material layer is provided, and the relevant preparation parameters are adjusted according to Table 1, the rest is the same as Example 1-1.
[0131] Comparative Example 3
[0132] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0133] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.
[0134]
[0135]
[0136]
[0137]
[0138] Table 2
[0139]
[0140] From Examples 1-1 to 1-29 and Comparative Examples 1 to 3, it can be seen that by adjusting the conductivity of the single-sided first pole piece to be less than or equal to the conductivity of the inner first pole piece, the lithium deposition and black spot area of the outer pole piece of the electrode assembly is smaller, and the 400cls capacity retention rate of the lithium ion battery is improved, indicating that the lithium ion battery of the present application can reduce the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle, and the lithium ion battery has good cycle performance. In Comparative Examples 1 and 2, only the second material layer is set on the outer single-sided first pole piece; the various parameters of the first material layer and the second material layer in Comparative Example 3 are exactly opposite to the various parameters of the first material layer and the second material layer in Example 1-1, and the various parameters of the third material layer in Comparative Example 3 are the same as the various parameters of the second material layer; the lithium deposition and black spot area of the lithium ion batteries in Comparative Examples 1 to 3 are larger; and the 400cls capacity retention rate is lower. However, the area of lithium plating and black spots on the outer first pole piece of the lithium-ion batteries in Examples 1-1 to 1-29 is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium plating on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion batteries have good cycle performance.
[0141] The types of the first active material and the second active material usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-13 that when the first active material and the second active material within the scope of the present application are selected, the lithium ion battery has a smaller area of lithium deposition and black spots on the outer first pole piece, and a higher capacity retention rate of 400cls, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is lower, and the lithium-ion battery has good cycle performance.
[0142] Dv50 and Dv99 of the first active material and Dv50 and Dv99 of the second active material usually affect the cycle performance of lithium-ion batteries. It can be seen from Examples 1-1 to 1-13, 1-28 and 1-29 that when Dv50 and Dv99 of the first active material and Dv50 and Dv99 of the second active material are within the scope of this application, the area of lithium deposition and black spots on the first outer pole piece of the lithium-ion battery is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.
[0143] The type and content of the first binder, and the type and content of the second binder usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-14 to 1-17 that when the first binder and the second binder within the scope of this application are selected, and the content of the first binder and the content of the second binder are adjusted within the scope of this application, the area of lithium deposition and black spots on the first outer pole piece of the lithium-ion battery is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.
[0144] The type and content of the first conductive agent, and the type and content of the second conductive agent usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-18 to 1-21 that when the first conductive agent and the second conductive agent within the scope of this application are selected, and the content of the first conductive agent and the content of the second conductive agent are adjusted within the scope of this application, the lithium ion battery has a smaller area of lithium deposition and black spots on the outer first pole piece, and a higher capacity retention rate of 400cls, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium ion battery has good cycle performance.
[0145] The type and content of the third active material usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-13 that when the third active material within the scope of this application is selected and the content of the third active material is regulated within the scope of this application, the area of lithium deposition and black spots on the first outer pole piece of the lithium-ion battery is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.
[0146] The thickness of the first material layer and the thickness of the second material layer usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-22 to 1-25 that when the thickness of the first material layer and the thickness of the second material layer are adjusted within the scope of this application, the area of lithium deposition and black spots on the first outer pole piece of the lithium-ion battery is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.
[0147] The thickness of the third material layer usually affects the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-26 and 1-27 that when the thickness of the third material layer is adjusted within the scope of this application, the area of lithium deposition and black spots on the first outer pole piece of the lithium-ion battery is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.
[0148] Table 3
[0149]
[0150] The type of the first pole piece usually affects the cycle performance of the lithium-ion battery. It can be seen from Example 1-1 and Example 2-1 that when the first pole piece is a positive pole piece or a negative pole piece, the area of lithium deposition and black spots on the outer first pole piece of the lithium-ion battery is small, and the 400cls capacity retention rate is high, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is low, and the lithium-ion battery has good cycle performance.
[0151] When the first pole piece is a negative pole piece, the type of the first active material and the type of the second active material usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-1 to 2-4 that when the first active material and the second active material within the scope of this application are selected, the lithium ion battery has a smaller area of lithium deposition and black spots on the outer first pole piece, and a higher capacity retention rate of 400cls, indicating that the risk of black spots and lithium deposition on the outer pole piece of the electrode assembly during the cycle is lower, and the lithium-ion battery has good cycle performance.
[0152] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0153] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0154] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A secondary battery, comprising an electrolyte, a housing and an electrode assembly of a laminated structure, wherein along the thickness direction of the electrode assembly, the electrode assembly comprises a first pole sheet, a second pole sheet and a diaphragm arranged between the first pole sheet and the second pole sheet; the electrode assembly further comprises a first pole tab assembly and a second pole tab assembly, the first pole tab assembly comprises a plurality of first pole tabs, the second pole tab assembly comprises a plurality of second pole tabs, the plurality of first pole tabs correspond to the first pole sheet one-to-one, and the plurality of second pole tabs correspond to the second pole sheet one-to-one; The first pole piece includes two outer first pole pieces and at least one inner first pole piece. Along the thickness direction of the electrode assembly, the two outer first pole pieces are respectively located on the outermost sides of the electrode assembly, and the inner first pole piece is located between the two outer first pole pieces. The first pole piece includes a first current collector and a first active material layer. The first current collector includes a first surface and a second surface that are arranged opposite to each other along the thickness direction of the electrode assembly. The first surface is closer to the housing than the second surface. The first active material layer is provided on both the first surface and the second surface of the inner first pole piece. At least one of the outer first pole pieces is a single-sided first pole piece, the first surface of the single-sided first pole piece is not provided with the first active material layer, the second surface of the single-sided first pole piece is provided with the first active material layer, the first active material layer provided on the second surface of the single-sided first pole piece is composed of a first material layer and a second material layer stacked, and the first material layer is located between the first current collector and the second material layer; The electrical conductivity of the single-sided first pole piece is AS / cm, the electrical conductivity of the inner first pole piece is BS / cm, and A≤B.
2. The secondary battery according to claim 1, wherein 0.3≤A / B≤1.
3. The secondary battery according to claim 2, wherein: 0.65≤A / B≤1.
4. The secondary battery according to any one of claims 1 to 3, wherein The first pole piece is a positive pole piece.
5. The secondary battery according to claim 4, wherein The first material layer includes a first active material, which includes at least one of lithium iron phosphate, lithium manganese iron phosphate or lithium manganese oxide; the second material layer includes a second active material, which includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, a nickel-cobalt-manganese ternary material or a lithium-rich manganese-based material.
6. The secondary battery according to claim 5, wherein The Dv50 of the first active material is 3 μm to 25 μm, and the Dv99 of the first active material is 10 μm to 65 μm; the Dv50 of the second active material is 4.5 μm to 24.5 μm, and the Dv99 of the second active material is 45 μm to 65 μm.
7. The secondary battery according to claim 4, wherein The first material layer includes a first binder, and the second material layer includes a second binder. The first binder and the second binder are independently selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polyvinylidene chloride, aramid, polyamide, polyacrylonitrile, acrylate polymer, styrene-butadiene rubber, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, pure acrylic emulsion or polyacrylic acid; based on the mass of the first material layer, the mass percentage of the first binder is 0.5% to 5%, and based on the mass of the second material layer, the mass percentage of the second binder is 0.4% to 5%.
8. The secondary battery according to claim 4, wherein The first material layer includes a first conductive agent, and the second material layer includes a second conductive agent, and the first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, carbon nanotubes, graphene or conductive graphite; based on the mass of the first material layer, the mass percentage of the first conductive agent is 1% to 10%, and based on the mass of the second material layer, the mass percentage of the second conductive agent is 1% to 10%.
9. The secondary battery according to claim 4, wherein The first active material layer arranged on the first surface and the second surface of the inner first pole piece is a third material layer, and the third material layer includes a third active material. The third active material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material or lithium-rich manganese-based material. Based on the mass of the third material layer, the mass percentage of the third active material is 85% to 98.6%.
10. The secondary battery according to claim 4, wherein The thickness of the first material layer is 20 μm to 60 μm, and the thickness of the second material layer is 20 μm to 150 μm.
11. The secondary battery according to claim 9, wherein The thickness of the third material layer is 80 μm to 250 μm.
12. The secondary battery according to claim 4, wherein 0.01≤B≤0.8。 13. The secondary battery according to claim 1 or 2, wherein: The thickness of the first current collector of the single-sided first pole piece is T1 μm, the thickness of the first current collector of the inner first pole piece is T2 μm, and T1 ≥ T2.
14. The secondary battery according to claim 13, wherein The first pole piece is a positive pole piece, 12≤T1≤25, 6≤T2≤16.
15. The secondary battery according to claim 13, wherein The first pole piece is a negative pole piece, 14≤T1≤25, 4≤T2≤16.
16. The secondary battery according to claim 4, wherein The shell is an aluminum-plastic film.
17. The secondary battery according to claim 1 or 2, wherein: The first electrode sheet is a negative electrode sheet, the first material layer includes a first active material, the electrical conductivity of the first active material is c S / cm, the second material layer includes a second active material, the electrical conductivity of the second active material is d S / cm, c<d; the first active material and the second active material are each independently selected from at least one of natural graphite, artificial graphite, intermediate phase microcarbon beads, hard carbon, soft carbon, silicon or silicon-carbon composites.
18. The secondary battery according to claim 17, wherein The shell is a steel shell.
19. A method for preparing the secondary battery according to any one of claims 1 to 18, comprising the following steps: Prepare at least one of the single-sided first pole pieces, at least one of the inner first pole pieces, a plurality of the second pole pieces, a plurality of the separators, the electrolyte and the shell, and assemble them to obtain the secondary battery; The method for preparing the single-sided first pole piece comprises the following steps: sequentially arranging the first material layer and the second material layer on the second surface of the first current collector to obtain the single-sided first pole piece; The method for preparing the inner first pole piece comprises the following steps: disposing the first active material layer on both the first surface and the second surface of the first current collector to obtain the inner first pole piece.
20. The preparation method according to claim 19, wherein: The first material layer includes a first active material, the electrical conductivity of the first active material is a S / cm, the second material layer includes a second active material, the electrical conductivity of the second active material is b S / cm, and a<b. 21 . An electronic device comprising the secondary battery according to claim 1 , or the secondary battery prepared by the preparation method according to claim 19 or 20.
Citation Information
Patent Citations
Negative pole piece, electrochemical device and electronic device
CN115132967A
Secondary battery and electronic device
CN117728043A
Battery cell and battery
CN219267725U
Electrode assembly and battery
CN220021170U
Cited By
Secondary battery and electric device
WO2026165796A1
